Sustainable beef cattle production: A comparative review between Australia and Indonesia - Latif, Amir; Koestoer, Raldi Hendro; Frimawaty, Evi (Holistic: Journal of Tropical Agriculture Sciences, 2026)
Background: Beef cattle farming is an important production activity to meet the protein needs of the community. Livestock produces carbon emissions that contribute to increasing global warming. The purpose of this article is to discuss the conditions of Indonesian beef cattle farming compared to the beef cattle farming system in Australia. Method: The method used in writing this paper is the Systematic Literature Review (SLR) with bibliometric content analysis. We analyze related to "keyword maps", "map of countries", and Scopus document publishing trends in sustainable beef cattle production studies for the period 2020 to 2025. The next stage, a comparison was made between two countries, namely Indonesia and Australia in the beef cattle production sector. Finding: The results of the bibliometric analysis showed that the top three countries with the highest link strength and leading in the study of sustainable beef cattle production were the United States, Brazil, and the United Kingdom. In terms of quantitative document publication, Indonesia is ranked fourth and Australia is ranked fifth. The results of the discussion showed that Indonesian beef production comes from small-scale beef cattle farms with slightly different cattle ownership from Australia, which is mostly industrial scale. Conclusion: One of the developments of sustainable beef cattle farming applied in Indonesia is the concept of integrating agricultural crops - cattle where plant waste is used as animal feed and livestock waste is processed into fertilizer for agricultural land. Novelty/Originality of this article: This study provides a contemporary bibliometric mapping (2020–2025) that identifies Indonesia as a top-tier contributor (ranked 4th globally) in sustainable beef production literature.